Activity-practical component in the structure of professional and personal experience of future music teachers (Pedagogy of Higher and Secondary Education, 2013)
Popovich N. M. Activity-practical component in the structure of professional and personal experience of future music teachers.In article the essence of an is active-practical component in structure of is professional-personal experience of the future teacher of music is analysed. The role of practical preparation of students in the conditions of a higher educational institution is proved.
Keywords: active-practical component; professional-personal experience; teacher of music; practical preparation